Editorial: Gender-intentional breeding case studies - Ashby, Jacqueline A.; Polar, Vivian; Tufan, H.A. (2025)
This editorial synthesizes 12 case studies of gender-sensitive intentional breeding, showing that integrating a gender perspective from early stages of the breeding cycle leads to concrete changes in objectives, methods, prioritized traits, and seed strategies. The cases demonstrate that women and men have partially distinct but overlapping preferences, and that responding to these preferences increases adoption and equity. The paper highlights methodological innovations (TRICOT, gender-sensitive PVS), institutional changes, and remaining challenges (funding, capacity building, metrics), aligning strongly with Systems Transformation, Crop Improvement, and Gender Equality.